A theology of complexity for Christian leadership in an uncertain future - Stanton, Graham D. (Practical theology, 2019)
This article engages with the challenge of uncertainty and uncontrollability in contemporary Christian leadership ministry by entering a theological conversation with the complexity sciences as applied to organisational theory. The correlational conversation identifies Ralph Stacey's theory of organisations as complex responsive processes of relating (CRPR) as consistent with covenantal ecclesiology and a theology of divine sovereignty in classical theism. A CRPR perspective on Christian leadership promotes participative ecclesiology and processes of dialogical formation. A theology of shalom is offered as a means of enabling leaders to persevere in the challenges of navigating complex times.